Direct measurement of a secular pulsation period change in the pulsating hot pre-white dwarf PG 1159-035 - Costa, Jose Eduardo da Silveira (1999)
GW Vir (PG 1159[035) is the prototype of the class of multiperiodic, nonradially pulsating hot white dwarfs, and shows a strong pulsation mode at 516 s. All measurements to date of the secular variation of the 516 s pulsation quote as best value P= (-2.49±0.06)]10 11 s s-ˡ. The original measurement gave two best solutions, and a x² analysis indicated that the quoted value was preferred at the level of 0.97 probability. On other hand, the best-developed models for planetary nebula nuclei (PNNs), using models from the asymptotic giant branch as starting points and simulating the observed mass loss, provide positive values for any model with log (L/Lʘ)<~ as PG 1159-035. This conflict between the measurement and the theoretical models has been a challenge to stellar evolution theory. Exploiting a much larger data set and computational techniques previously unavailable, we show that the earlier analysis of the data grossly underestimated the true uncertainties due to interferences between frequencies. Using new data along with the old, and more accurate statistical methods, we calculated the secular period change of the 516 s pulsation, and obtained a positive value : P=(+13.07±0.03)]10 -11 s s-ˡ. We show that three additional methods yield the same solution. This new value was the second best of the original possible solutions ; it was eliminated on the basis of statistical arguments that we show to be invalid. It is an order of magnitude larger than the theoretical predictions. Additionally, from rotational splitting analysis, we were able to estimate, for the first time, a limit to the secular variation of the rotational period P rot=(-1.0±3.5)]10 -11 s s-ˡ, leading to a contraction timescale upper limit of |tr-ˡ|=|R/R| < 48 x 10 11 s-ˡ with 99.5% probability.